2014
DOI: 10.1038/ncb3071
|View full text |Cite
|
Sign up to set email alerts
|

DAF-16/FOXO and EGL-27/GATA promote developmental growth in response to persistent somatic DNA damage

Abstract: Genome maintenance defects cause complex disease phenotypes characterized by developmental failure, cancer susceptibility, and premature aging. It remains poorly understood how DNA damage responses function during organismal development and maintain tissue functionality when DNA damage accumulates with aging. Here we show that the FoxO transcription factor DAF-16 is activated in response to DNA damage during development while the DNA damage responsiveness of DAF-16 declines with aging. We find that in contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(123 citation statements)
references
References 60 publications
5
114
0
Order By: Relevance
“…The absence of transcriptional activators such as med-1/2, end-3, or end-1 in non-E-cells implies that there may be other GATA-binding transcriptional activators present outside of the nascent endoderm during early embryogenesis (Budovskaya et al, 2008; Gilleard, Shafi, Barry, & McGhee, 1999; Mueller et al, 2014; Murphy et al, 2003). We found that in a minimal 613 bp promoter context, secondary auxiliary HGATAR motif(s) in the 4G region are necessary for producing low-level stochastic transcription (Table 1 613:A4G; Fig 3D).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of transcriptional activators such as med-1/2, end-3, or end-1 in non-E-cells implies that there may be other GATA-binding transcriptional activators present outside of the nascent endoderm during early embryogenesis (Budovskaya et al, 2008; Gilleard, Shafi, Barry, & McGhee, 1999; Mueller et al, 2014; Murphy et al, 2003). We found that in a minimal 613 bp promoter context, secondary auxiliary HGATAR motif(s) in the 4G region are necessary for producing low-level stochastic transcription (Table 1 613:A4G; Fig 3D).…”
Section: Discussionmentioning
confidence: 99%
“…In C. elegans , the involvement of the two NER sub pathways differs spatially and temporally [19,20,26]. TC-NER is the major repair pathway in transcriptionally active late embryos and early larval stages, whereas GG-NER takes over the role in early embryos and the germ cells, which are highly proliferative.…”
Section: Resultsmentioning
confidence: 99%
“…TC-NER activity is required for resisting UV-induced DNA lesions during adulthood [20,26,28,29]. We further investigated whether ZK742.2 is involved in the UV-survival of adult worms, which consists almost entirely of post-mitotic cells, except for the germline that undergo mitotic and meiotic cell divisions.…”
Section: Resultsmentioning
confidence: 99%
“…There is emerging evidence that these pathways are also affected by DNA damage (Niedernhofer et al 2006 ;Mueller et al 2014 ) and might be connected to the immune system (Guo et al 2014 ) and that they control maintenance of pluripotency of stem cells (Bendall et al 2007 ).…”
Section: Stem Cell Rejuvenation: Mechanistic Prerequisitesmentioning
confidence: 98%